Electrooptical Determination of Polarizability for On-Line Viability and Vitality Quantification of Lactobacillus plantarum Cultures - Pellicer-Alborch, Klaus; Angersbach, Alexander; Neubauer, Peter; Junne, Stefan (Frontiers in Bioengineering and Biotechnology, 2018)
The rapid assessment of cell viability is crucial for process optimization, e.g. during media selection, determination of optimal environmental growth conditions and for quality control. In the present study, the cells’ electric anisotropy of polarizability (AP) as well as the mean cell length in Lactobacillus plantarum batch and fed-batch fermentations were monitored with electrooptical measurements coupled to fully automated sample preparation. It was examined, whether this measurement can be related to the cells’ metabolic activity, and thus represents a suitable process analytical technology. It is demonstrated that the AP is an early indicator to distinguish between suitable and unsuitable growth conditions in case of a poor energy regeneration or cell membrane defects in L. plantarum batch and fed-batch cultivations. It was shown that the applied method allowed the monitoring of physiological and morphological changes of cells in various growth phases in response to a low pH-value, substrate concentration changes, temperature alterations, exposure to air and nutrient limitation. An optimal range for growth in batch mode was achieved, if the AP remained above 25 ∙ 10-28 Fm2 and the mean cell length at approx. 2.5 µm. It was further investigated, in which way the AP develops after freeze-drying of samples, which were taken in different cultivation phases. It was found that the AP increased most rapidly in resuspended samples from the retardation and late stationary phases, while samples from the early stationary phase recovered slowly. Electrooptical measurements provide valuable information about the physiologic and morphologic state of L. plantarum cells, e.g. when applied as starter cultures or as probiotic compounds.